2019
DOI: 10.1002/mar.21298
|View full text |Cite
|
Sign up to set email alerts
|

Do gender identities of femininity and masculinity affect the intention to buy ethical products?

Abstract: This study shows that gender identity affects ethical intentions. We investigate the intention to purchase ethical products through a survey study among young consumers in Italy. Measures of planned behavior, internal ethics, self-identity, and moral harm, together with proxies for individual gender identities of femininity and masculinity are included in our model of intention to purchase ethically. Results show that femininity significantly increases ethical intent, whereas masculinity has an opposite effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 87 publications
2
39
0
Order By: Relevance
“…Men seem to be particularly resistant to purchase products that signal femininity to maintain their gender identity (Antonetti & Maklan, 2016; Avery, 2012; Brough et al, 2016; Gal & Wilkie, 2010; Gill & Lei, 2018; Morris & Cundiff, 1971; Pinna, 2019; White & Dahl, 2006). For example, Shang and Peloza (2016) showed that consumption of ethical alternatives communicates higher femininity to external observers, which could be threatening for male consumers.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Men seem to be particularly resistant to purchase products that signal femininity to maintain their gender identity (Antonetti & Maklan, 2016; Avery, 2012; Brough et al, 2016; Gal & Wilkie, 2010; Gill & Lei, 2018; Morris & Cundiff, 1971; Pinna, 2019; White & Dahl, 2006). For example, Shang and Peloza (2016) showed that consumption of ethical alternatives communicates higher femininity to external observers, which could be threatening for male consumers.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Women appear to have stronger attitudes towards environmental preservation and a higher likelihood to adopt eco‐friendly consumption behaviors than men (Davidson & Freudenburg, 1996; Hunter, Hatch, & Johnson, 2004; Xiao & McCright, 2015; Zelezny, Chua, & Aldrich, 2000). On the other hand, men seem to show some reluctance to engage in eco‐friendly consumption and ethical consumption in general because it would be associated with femininity (Brough et al, 2016; Pinna, 2019; Shang & Peloza, 2016; Swim et al, 2019), and this green‐feminine stereotype could constitute a threat to their masculine identity. But does this stereotype always pose a threat to men?…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the gender role in response to COVID-19 measure is important as previous studies have concluded that behaviour is gendered and marketers-in this case social marketers-have been long facilitating inidividual's self-expression need by associating specific behaviour or object with gender characteristics (Pinna 2020;Neale et al 2016). Such that, individuals are expected to prefer behaviour or object that are consistent with their self-concept (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such that, individuals are expected to prefer behaviour or object that are consistent with their self-concept (e.g. femininity or masculinity) (Pinna 2020). Consequently and in addition to the theoretical contributions, understanding gender differences in response toward COVID-19 measures will help marketers to embrace the dynamics of reality (Sushil 1997;Ganuthula and Sinha 2019;Evans and Bahrami 2020) and design an innovative approach (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of planned behavior describes that attitudes, subjective norms, and perceived behavioral control come together to influence behavioral intentions, which then influence participation in a behavior (Ajzen, 1991). This theory has been used extensively in the marketing and consumer psychology literature to explain consumer behavior (e.g., Bansal & Taylor, 2002; Kidwell & Jewell, 2003; Lim & Dubinsky, 2005; Nocella et al, 2012; Pinna, 2020; Thorbjørnsen et al, 2007). The theory has also been used widely within the recreation literature to understand the behavior of recreationists (e.g., Kidd et al, 2015; Lawhon et al, 2013; Reigner & Lawson, 2009; Schwartz et al, 2018; Vagias et al, 2014).…”
Section: Theory Of Planned Behavior and Reasons For Participating In mentioning
confidence: 99%